Effects of Motivational Interviewing or an Educational Video on Knowledge about HIV/AIDS, Health Beliefs and Antiretroviral Medication Adherence among Adult Thais with HIV/AIDS. - Maneesriwongul, Wantana; Prajanket, Ong-On; Saengcharnchai, Pichai (Pacific Rim International Journal of Nursing Research)
Patient adherence to antiretroviral therapy is linked to suppression of viral replication. Inadequate adherence to the use of antiretroviral therapy may lead to failure of treatment outcomes and viral resistance. The purpose of this study was to examine the effectiveness of two interventions (motivational interviewing, along with counseling, and an educational video) on knowledge about HIV/AIDS, health beliefs and adherence to antiretroviral therapy. The study used a pretest/posttest design involving 90 adults with HIV/AIDS who were randomly assigned to one of three groups: motivational interview (n = 30); educational video (n = 30); or, usual care (n = 30). Subjects in all three groups had similar demographic and health status characteristics. Data were obtained using four questionnaires that assessed the subjects': demographic and health status characteristics; knowledge about HIV/AIDS; health beliefs; and, antiretroviral therapy adherence. The usual care group showed significant improvements in knowledge about HIV/ AIDS and adherence to antiretroviral therapy adherence, but no significant improvement in health beliefs. However, following completion of the two interventions, significantly greater improvements were noted in knowledge about HIV/AIDS, health beliefs and, antiretroviral therapy adherence among subjects in the motivational interviewing, along with counseling, group and the educational video group, compared to those in the usual care group. No significant differences were found, between the motivational interviewing, along with counseling, group and the educational video group, regarding these factors. The findings suggest the effectiveness of using motivational interviewing, along with counseling, or an educational video for enhancing adherence to antiretroviral therapy.